Rasendra maṅgalam - Nāgārjuna; Śarmā, Hari Śaṅkara (Rasendramaṅgalam of Nāgārjuna, 2003)
Verse work on Ayurvedic system in Indic medicine describing the therapeutic uses of metals and other minerals; Sanskrit text with Hindi and English translation.
Includes indexes.
v. 1. Adhyāya 1-4
Verse work on Ayurvedic system in Indic medicine describing the therapeutic uses of metals and other minerals; Sanskrit text with Hindi and English translation.
English, Hindi, and Sanskrit.
Keywords: Medicine, Ayurvedic. / http://id.loc.gov/authorities/subjects/sh85083119; Metals / Therapeutic use. / http://id.loc.gov/authorities/subjects/sh85084250